Perencanaan Komunikasi Akun Instagram Gerakan Sosial Komunitas PhD Mama Indonesia - Anisa, Dian Dwi (Program Studi Ilmu Komunikasi Universitas Negeri Padang, 2023)
Mothers who pursue higher education often face negative stereotypes due to patriarchal culture. Therefore, it is important to advocate for mother-student groups and provide them with support. The PhD Mama Indonesia community is one such support system that spreads its ideas through various internet-based media platforms. This paper examines the communication planning of the PhD Mama Indonesia social movement community in conducting digital activism, specifically through their Instagram account @phdmamaindonesia. The research is qualitative, utilizing data collection techniques such as interviews with the head of the Creative Design and Instagram Division, observation of uploads on Instagram @phdmamaindonesia, and supporting literature. The research findings indicate that the community employs four stages of communication planning, namely the Share, Optimize, Manage, and Engage stages, as proposed by the Circular Model of SoMe by Regina Luttrell. However, the implementation of these stages was not optimal in some cases due to the voluntary membership and lack of external funding assistance of PhD Mama Indonesia community. Their Instagram account remains active due to the common interests of the members, which is typical of digital activism.